2020
DOI: 10.1039/d0cp01437k
|View full text |Cite
|
Sign up to set email alerts
|

A surface modifier enhances the performance of the all-inorganic CsPbI2Br perovskite solar cells with efficiencies approaching 15%

Abstract: All-inorganic perovskite solar cells (PSCs) are attracting considerable attention due to their promising thermal stability, but their inferior power-conversion efficiencies (PCE) hinder their realistic application. Here, we propose an approach...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…This combined processing led to producing smooth and fewerdefect perovskite films and achieving a champion PCE of 16.07% with impressive stability. 14 Similarly, the additional post-treatments of CsPbI 2 Br films by cesium bromide, 15 methylammonium bromide, 16 and methylammonium iodide have been tried to improve the interface at the grain boundaries of the perovskite absorber layer, and the interfacial recombination-related energy losses have been significantly eliminated. 17 Doping engineering of I-PSCs has also been studied in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This combined processing led to producing smooth and fewerdefect perovskite films and achieving a champion PCE of 16.07% with impressive stability. 14 Similarly, the additional post-treatments of CsPbI 2 Br films by cesium bromide, 15 methylammonium bromide, 16 and methylammonium iodide have been tried to improve the interface at the grain boundaries of the perovskite absorber layer, and the interfacial recombination-related energy losses have been significantly eliminated. 17 Doping engineering of I-PSCs has also been studied in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…This combined processing led to producing smooth and fewer-defect perovskite films and achieving a champion PCE of 16.07% with impressive stability . Similarly, the additional post-treatments of CsPbI 2 Br films by cesium bromide, methylammonium bromide, and methylammonium iodide have been tried to improve the interface at the grain boundaries of the perovskite absorber layer, and the interfacial recombination-related energy losses have been significantly eliminated . Doping engineering of I-PSCs has also been studied in recent years. The Pb 2+ metal cations are partially substituted by Sr 2+ , Ge 2+ , Mn 2+ , Ba 2+ , Eu 3+ , and Nb 5+ metal cations to improve the stability of the black α-phase by passivating the trap states and reducing the nonradiative losses in solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…While the stability is being improved, the PCE (17.46%) [21] of α-phase CsPbI 2 Br is still far below the Shockley-Queisser (SQ) limit (24.75%) [22] and thus inferior to its hybrid organic-inorganic counterparts.Recently, it was observed that surface defect passivation can effectively enhance the PCE of the CsPbI 2 Br PSC. [23][24][25][26][27][28][29] Annihilation of surface I and Br vacancies via the incorporation of external anions was proposed to be the root cause of the improved performance, [30] but the underlying mechanism is still under debate. Some researchers suggested that the interactions with external anions could suppress the migration of surface ions in CsPbI 2 Br, thus alleviating the hysteresis effect, [31] while others ascribed the improvement to the reduction of parasitic nonradiative charge-carrier recombination centers formed by surface point defects.…”
mentioning
confidence: 99%
“…[33][34][35][36] This defect can induce detrimental deep-level defect states in the bandgap. [23,24,28,[37][38][39][40] Several reports have indicated that alkali metal halide can electronically passivate the Pb Br defect at the surface and prolong the durability of the solar cells. [37][38][39][40] In the passivation process, the ions are adsorbed at the surface vacant sites with sufficiently low kinetic barriers, which is similar to ion batteries, but different in that the adsorption process is irreversible while ionic intercalation in batteries is reversible.…”
mentioning
confidence: 99%
“…This is generally caused by the employment of highly volatile organic components, e.g. methylammonium cation (MA+) or formamidinium cation (FA+), , which upon thermal annealing or other external stimuli accelerate the decomposition of perovskites. , To tackle these critical issues, a series of heat-tolerant inorganic CsPbX 3 (X: I, Br, or mixed halides) perovskites have been developed for PSCs. Apart from the supreme thermal stability, these inorganic perovskite counterparts also exhibit satisfactory material robustness upon exposure to oxygen or ultraviolet irradiation. , Among the inorganic perovskite family, mixed halide CsPbI 2 Br has been concentrated, given its structural stableness and low-temperature phase transition characteristics, favorable for use in PSCs.…”
mentioning
confidence: 99%